(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In this article, in the second half of the 17th century - the beginning of the 19th century, on the territory of the Bukhara Emirate, Khiva and Kokan khanates, there was the emergence of local pottery schools with their own distinctive features, the main schools of pottery. Uzbek glazed ceramics, general principles of development and local features of the centers are presented.